Oral Paricalcitol for the Treatment of Secondary Hyperparathyroidism in Patients on Hemodialysis or Peritoneal Dialysis - Ross, Edward A.; Tian, Jin; Abboud, Hanna; Hippensteel, Richard; Melnick, Joel Z.; Pradhan, Rajendra S.; Williams, Laura A.; Hamm, L. Lee; Sprague, Stuart M. (American journal of nephrology, 2008)
Background/Aims: Secondary hyperparathyroidism is a common complication of chronic kidney disease, resulting from inactivation of vitamin D receptor signaling and phosphate retention. Selective activation of vitamin D receptors with intravenous paricalcitol significantly reduced parathyroid hormone (PTH) levels with no significant hypercalcemia or hyperphosphatemia in predialysis and hemodialysis (HD) patients. This study investigates the effects of oral paricalcitol to reduce PTH in patients receiving chronic HD and peritoneal dialysis (PD). Methods: Eighty-eight patients were randomized in double-blind fashion to receive paricalcitol or placebo for 12 weeks. The dose of the study drug was adjusted weekly using the previous week’s intact PTH (iPTH) level as well as calcium and Ca × P product levels. The primary end points were efficacy (two consecutive iPTH decreases of ≧30%) and safety (two consecutive calcium measurements >11.0 mg/dl). Markers of biochemical bone activity were followed. Results: Demographic characteristics were similar between treatment groups. The mean paricalcitol doses (three times a week) over the entire treatment period for subjects with baseline iPTH ≤500 pg/ml and iPTH >500 pg/ml were 3.9 and 7.6 µg, respectively. A statistically significant decrease in iPTH was seen after week 1, with a mean 30% reduction occurring by week 3. A significantly greater proportion of both HD and PD paricalcitol subjects [83% (33/40) and 100% (18/18), respectively] achieved two consecutive ≧30% decreases in iPTH. The treatment groups were not statistically different in regard to the hypercalcemia safety end point. Phosphate binder use and mean serum phosphorus levels were not different between the treatment groups. The markers of bone activity improved in the treated subjects and worsened in those on placebo. Conclusion: Paricalcitol provides a rapid and sustained reduction of PTH in both HD and PD patients with minimal effect on serum calcium and phosphorus and no significant difference in adverse events as compared with placebo.